2020
DOI: 10.1016/j.scitotenv.2020.141369
|View full text |Cite
|
Sign up to set email alerts
|

Where we missed? Middle East Respiratory Syndrome (MERS-CoV) epidemiology in Saudi Arabia; 2012–2019

Abstract: MERS-CoV first case was reported on 23rd November 2012 in Saudi Arabia, Since, then MERS has remained on World Health Organization (WHO) Blueprint list and declared pandemic. This study was conducted on MERS lab confirmed cases reported to Ministry of Health, Saudi Arabia and WHO for year 2012–2019. The epidemiology was investigated based on infection rate, death rate, case fatality rate, Gender, Age group, and Medical conditions (Comorbid and Symptomatic). The overall median age of infected male was 58 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although the MERS‐CoV was diagnosed as the human respiratory pathogen in June 2012 in Saudi Arabia, as of April 15, 2020, globally a total of 2468 MERS‐CoV confirmed cases were reported (Khan et al., 2020 ). The MERS‐CoV, which is a betacoronavirus belonging to lineage C, is an enveloped virus with a single‐stranded RNA genome with a size of about 30 kb.…”
Section: An Overview Of Coronavirusmentioning
confidence: 99%
“…Although the MERS‐CoV was diagnosed as the human respiratory pathogen in June 2012 in Saudi Arabia, as of April 15, 2020, globally a total of 2468 MERS‐CoV confirmed cases were reported (Khan et al., 2020 ). The MERS‐CoV, which is a betacoronavirus belonging to lineage C, is an enveloped virus with a single‐stranded RNA genome with a size of about 30 kb.…”
Section: An Overview Of Coronavirusmentioning
confidence: 99%
“…MERS-CoV patients were hospitalized for an average of 18 days, two-thirds (64%) developed organ complications, more than a quarter (29%) developed severity requiring ventilation, and 21% died at hospital. Our findings on key characteristics of MERS-CoV (percent with comorbidity, days of hospitalization, percent who require ventilation, case fatality rate) are in the lowest range of values reported to date [ 7 , 15 , 34 , 35 ]. Our report updates information on the most common concurrent infections that are likely to be observed in settings that have implemented most advanced infection control measures.…”
Section: Discussionmentioning
confidence: 68%
“…This would mean that men aged 40-60 years in Saudi Arabia have greater exposure to the source of infection than women. Further, the high prevalence of metabolic diseases -related pathophysiology in men [ 14 , 34 , 35 , 40 , 41 ] predisposes them to the expression of MERS-CoV disease. KSA has the 4 th largest camel to population ratio (1 to 40 persons) after Somalia, Mauritania (1 to 1.4) and Sudan (1 to 8.6) [ 39 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 It is worth mentioning that Middle East Respiratory Syndrome-related Coronavirus (MERS-CoV) is not included in the respiratory panel test in our hospital. Indeed, Khan et al 7 found that the MERS-CoV infection ratio have significantly declined during 2016-2019 with the least infected ages on average being below 20 years old (ref).…”
Section: Discussionmentioning
confidence: 99%